RANCANG BANGUN SISTEM INFORMASI PUSKESMAS UMBAN SARI BERBASIS WEB - Iskandar, Deni; Nasution, Nurliana; Zamsuri, Ahmad (LPPM STMIK Royal Kisaran, 2024)
Abstract: Umban Sari Community Health Center still uses handwriting to process data on young children, causing reports to be lost or damaged. In general, community health centers face various obstacles in recording and reporting. Based on the results of the interview, there were various obstacles related to recording and reporting the results of activities, namely the handwritten health center information system and the reporting warehouse which was quite messy and cramped. This system is a prototype method. Prototyping is a systematic development method that uses an approach to build a program quickly and gradually so that users can launch it immediately. Data from field studies were collected by researchers directly from the Umban Sari Community Health Center, Rumbai Regency. The author conducted interviews to obtain information about the process carried out, observations to confirm and perfect the material, and obtain direct information about the research. The aim of the system analysis stage is to create a basis for creating or improving existing systems. The results of the analysis can be used to create or modify a more effective and efficient system.Keywords: Health Center, Information System, Modeling Abstrak : Puskesmas Umban Sari masih menggunakan tulisan tangan dalam mengolah data anak kecil sehingga menyebabkan laporan hilang atau rusak. Secara umum, puskesmas menghadapi berbagai hambatan dalam pencatatan dan pelaporan. Berdasarkan hasil wawancara, terdapat berbagai kendala terkait pencatatan dan pelaporan hasil kegiatan, yaitu sistem informasi puskesmas yang ditulis tangan dan gudang pelaporan yang cukup berantakan dan sempit. sistem ini adalah metode prototipe. Prototyping adalah metode pengembangan sistematis yang menggunakan pendekatan untuk membangun sebuah program secara cepat dan bertahap sehingga pengguna dapat segera mengevaluasinya. Data hasil studi lapangan dikumpulkan oleh peneliti langsung dari Puskesmas Umban Sari Kabupaten Rumbai. Penulis melakukan wawancara untuk memperoleh informasi mengenai proses yang dilakukan, observasi untuk mengkonfirmasi dan menyempurnakan materi, serta memperoleh informasi langsung mengenai penelitian.Tujuan dari tahap analisis sistem adalah untuk membuat landasan dalam membuat atau memperbaiki sistem yang sudah ada. Hasil analisis dapat digunakan untuk membuat atau memodifikasi sistem yang lebih efektif dan efisien.Kata Kunci: Pemodelan, Puskesmas, Sistem Informasi